2005
DOI: 10.1165/rcmb.2003-0341oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Induces DNA Damage but Not Apoptosis in Human Bronchial Epithelial Cells

Abstract: Whether DNA damage caused by cigarette smoke leads to repair or apoptosis has not been fully elucidated. The current study demonstrates that cigarette smoke induces single-strand DNA damage in human bronchial epithelial cells. Cigarette smoke also stimulated caspase 3 precursors as well as intact poly (ADP-ribose) polymerase (PARP) production, but did not activate caspase 3 or cleave PARP, while the alkaloid camptothecin did so. Neither apoptosis nor necrosis was induced by cigarette smoke when the insult was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 26 publications
(28 reference statements)
13
78
0
Order By: Relevance
“…This may be one reason why lung cancer is prone to occur in smokers. Higher CSE concentration or longer periods of stimulation with CSE leads to apoptosis or even necrosis, consistent with the results from other researchers [35,36]. Besides treatment factors, cell type [37] is also one factor that can affect cell apoptosis or necrosis when stimulated.…”
Section: Discussionsupporting
confidence: 91%
“…This may be one reason why lung cancer is prone to occur in smokers. Higher CSE concentration or longer periods of stimulation with CSE leads to apoptosis or even necrosis, consistent with the results from other researchers [35,36]. Besides treatment factors, cell type [37] is also one factor that can affect cell apoptosis or necrosis when stimulated.…”
Section: Discussionsupporting
confidence: 91%
“…Although the role of apoptosis in CSE-induced cell death remains incompletely understood (33)(34), we demonstrate that CSE exposure induces an extrinsic apoptotic pathway involving DISC formation and downstream activation of caspases-8/caspase-3 in MRC-5 cells (Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that CSE induces reversible DNA damage and that oxidants play a role in this damage in human lung fibroblasts and epithelial cells (20,23). The reduced mRNA induction of RIG-I could be caused by direct damage to the DNA segment of this important pathogen sensor.…”
Section: Discussionmentioning
confidence: 99%